Nordic walking jako forma aktywności fizycznej w opinii mieszkańców Poznania = Nordic walking as a form of physical activity in the opinion of the residents of Poznań - Jarecka, Paulina; Fąk, Tadeusz; Skrzypczyk, Teresa (Journal of Education, Health and Sport, 2016)
Jarecka Paulina, Fąk Tadeusz, Skrzypczyk Teresa. Nordic walking jako forma aktywności fizycznej w opinii mieszkańców Poznania = Nordic walking as a form of physical activity in the opinion of the residents of Poznań. Journal of Education, Health and Sport. 2016;6(12):376-383. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.202456 http://ojs.ukw.edu.pl/index.php/johs/article/view/4070 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 14.12.2016. Nordic walking jako forma aktywności fizycznej w opinii mieszkańców Poznania Nordic walking as a form of physical activity in the opinion of the residents of Poznań Paulina Jarecka1, Tadeusz Fąk, Teresa Skrzypczyk2 1 Katedra Pedagogiki Kultury Fizycznej, Akademia Wychowania Fizycznego we Wrocławiu 2 Instytut Turystyki, Wyższa Szkoła Bankowa we Wrocławiu Słowa kluczowe: formy aktywności fizycznej, nordic walking, Poznań Key words: forms of physical activity, nordic walking, Poznań Streszczenie Tworząca się w Polsce moda na aktywny wypoczynek sprawia, że w społeczeństwie wzrasta zainteresowanie różnymi formami aktywności fizycznej. U podłoża tych zachowań stoi dobroczynny wpływ na zdrowie psychofizyczne, większa ilość czasu wolnego oraz szeroka możliwość korzystania z różnorodnych jej form. W ciągu ostatniej w tej sferze coraz większe zainteresowanie zyskuje nordic walking. Autorzy niniejszego opracowania postanowili zatem zgłębić tą tematykę na podstawie badań osób mieszkających w Poznaniu. Celem przeprowadzonych badań było ustalenie motywacji oraz profilu społeczno-demograficznego uczestników zajęć z nordic walking. Istotne było również ukazanie pozytywnych aspektów wynikających z uprawiania tej formy aktywności fizycznej w ocenie respondentów. Badania przeprowadzono w 2016 roku metodą sondażu diagnostycznego, w którym wykorzystano technikę ankietowania, narzędziem badawczym był kwestionariusz ankiety. Uczestnikami zajęć były w zdecydowanej większości kobiety posiadające wykształcenie wyższe. Głównym motywem uczestnictwa w zajęciach dla większości badanych była troska o zdrowie i poprawa samopoczucia. Przeprowadzone badania wykazały pozytywny wpływ nordic walking na sferę psychofizyczną. Uczestnicy zajęć postrzegają tę formę aktywności jako integralną część swojego życia, zaś zdecydowana większość badanych uczestniczy w zajęciach dla przyjemności. Abstract The fashion for active rest, which is created in Poland, is causing in society increased interest in various forms of physical activities. At the very core of these behaviors are beneficial influence on psycho-physical health and increased amount of free time, as well as unlimited availability of such forms. The authors of the study decided to diagnose this problem in the group of residents living in Poznan. The goal of the research was to determinate the motivation and socio-demographic profile of the Poznan residents’ participating in the nordic walking classes. Furthermore, to highlight positive aspects that arise from practicing this form of physical activity. The study was conducted in 2016 using method of diagnostic survey, in which technique of polling and questionnaire as a research tool had been used. The vast majority of participants of the classes were women with higher education degree. Major motivation for participating in classes for most of the respondents was care about health and improvement of wellbeing. Conducted studies have shown positive influence of nordic walking on psycho-physical aspect of life. The participants of the classes perceive this form of physical activity as the integral part of their lives. The vast majority of respondents participate in the classes for pleasure.